1991
DOI: 10.1111/j.1469-8749.1991.tb14899.x
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculous Hydrocephalus: Comparison of Different Treatments With Regard to Icp, Ventricular Size and Clinical Outcome

Abstract: SUMMARY The effect of different treatment regimes on intracranial pressure (ICP), degree of hydrocephalus and clinical outcome was evaluated in 81 children with tuberculous meningitis. 24 children underwent CSF shunting, while 57 with communicating hydrocephalus were randomly assigned to three treatment groups: antituberculous drugs only; or additional intrathecal hyaluronidase or oral acetazolamide and furosemide in addition to antituberculous treatment. The addition of acetazolamide and furosemide was signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
43
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(46 citation statements)
references
References 18 publications
0
43
1
2
Order By: Relevance
“…Studies have shown that clinical diagnosis of the presence and degree of raised ICP is unreliable, especially in children with closed anterior fontanels [16]. The value of CT imaging is limited by the poor correlation between the degree of hydrocephalus (ventricular size) and ICP [16]. Similarly, in this study, no correlation was found between ventricular size on CT and the degree of raised ICP (p=0.73).…”
Section: Discussioncontrasting
confidence: 63%
See 2 more Smart Citations
“…Studies have shown that clinical diagnosis of the presence and degree of raised ICP is unreliable, especially in children with closed anterior fontanels [16]. The value of CT imaging is limited by the poor correlation between the degree of hydrocephalus (ventricular size) and ICP [16]. Similarly, in this study, no correlation was found between ventricular size on CT and the degree of raised ICP (p=0.73).…”
Section: Discussioncontrasting
confidence: 63%
“…Inhibition of CSF flow occurs once 99.5 % of choroid plexus carbonic anhydrase is inhibited [21]. In children with communicating tuberculous hydrocephalus, acetazolamide and furosemide in combination have been found to be more effective in achieving normal ICP than antituberculous drugs alone [16]. In this study, rapid normalization of ICP occurred within 7 days of therapy in all 10 cases of communicating tuberculous hydrocephalus who had elevated ICP (Fig.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The method that is most effective for treating TBM-associated hydrocephalus has not been specifically studied to date. For individuals with communicating hydrocephalus, the addition of acetazolamide and furosemide to standard antituberculosis therapy is superior to antibiotics alone (181). For those with noncommunicating hydrocephalus, some form of external drainage and/or VPS is needed.…”
Section: Surgical Therapymentioning
confidence: 99%
“…Distinction between the two is important in terms of potential treatment options. Communicating hydrocephalus is more common in TBM (82%) [107].…”
Section: Raised Intracranial Pressure and Hydrocephalusmentioning
confidence: 99%